DEVELOPMENT OF SOFT SKILLS AND HARD SKILLS FOR CLEANING STAFF: STUDY ON CLEANLINESS OF PRIVATE UNIVERSITIES IN SURABAYA - Soetedja, Venny (Review of Management and Entrepreneurship, 2020)
Improving hard skills and soft skills can be done through appropriate and well-scheduled training. So, the purpose of this study is to look at differences in increasing the competence of hard skills and soft skills in cleaning staff at private universities through learning control classes and experimental classes. The method used is a quasi-experimental design with the Non-Equivalent Control Group Design. Respondents in this study were 50 cleaning staff of a private university in Surabaya, Indonesia. The results showed that the achievement of the experimental class assessment is significantly different compared to the achievement of the control class assessment regarding soft skills and hard skills.